2016
DOI: 10.1186/s12955-016-0551-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with Barrett’s esophagus

Abstract: BackgroundGastroesophageal reflux disease (GERD) has become a major health problem globally, affecting patients’ health-related quality of life (HRQOL). Barrett’s esophagus (BE) is a precancerous lesion associated with GERD. BE patients might not only suffer from HRQOL losses by GERD but also face psychological distress due to the increased risk of developing cancer. However, the majority of patients in Asia have shorter BE segment which is different from the West. This study aimed to determine whether the HRQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…A recent study enrolling 84 BE cases in Taiwan found BE had significantly poor HRQoL, based on WHOQOL-BREF scores, compared with healthy controls. The difference existed in the physical domain, but not in the social or psychological domains [ 17 ]. However, the HROoL of each subgroup of BE patients, or the severity of coexisting GERD symptoms, were not evaluated in the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study enrolling 84 BE cases in Taiwan found BE had significantly poor HRQoL, based on WHOQOL-BREF scores, compared with healthy controls. The difference existed in the physical domain, but not in the social or psychological domains [ 17 ]. However, the HROoL of each subgroup of BE patients, or the severity of coexisting GERD symptoms, were not evaluated in the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous cohort study by Chang et al, which found that patients with BE overall have a worse QOL compared to the general population. 19 A second prospective cohort study by Kulig et al described that the impairment in QOL among patients with BE to be similar to that of patients with GERD. 20 While chronic GERD is an important factor in the development of BE, patients with BE represent a unique subset of GERD patients.…”
Section: Discussionmentioning
confidence: 97%
“…Yet, frequently BE patients have insufficient understanding of the disease, inaccurate perceptions of cancer risk, and an unnecessary psychological burden, all amenable to clarification and better guidance (55). In a Taiwanese study, 84 BE patients were compared with 168 healthy adults and were found to have significantly lower QoL scores, particularly in pain, discomfort, sleep and rest and dependence on medications or treatments but there were no significant differences in social and psychological domains (56).…”
Section: Qolmentioning
confidence: 99%